(untitled) (Texas Journal of Medical Science, 2024)
The study of QoL in pediatrics is of undoubted interest, as this opens up the possibility of a comprehensive analysis and study of the child’s health. The use of indicators of the quality of life in the practice of a doctor can become an additional criterion for assessing the state of health and development of the child, the effect of the disease on the well-being of the child, as well as assessing the effectiveness of therapy